Marketing Analysis of Sheep in People's Farms, Stabat District, Langkat Regency - Syahfitri; Hasnudi; GAW Siregar (Jurnal Peternakan Integratif, 2022)
This study aims to determine marketing channels, marketing costs, analysis of marketing margins and marketing efficiency of sheep in the people's farms of Stabat District. This research was conducted in Stabat District, Langkat Regency in October-November 2021. This study took 3 villages as the research sample locations, namely Sidomulyo, Paya Mabar and Dendang villages, while the samples were collectors and retailers by snowball sampling. Data was collected by interview technique using a questionnaire. Data analysis includes market behavior and marketing margins. The results showed that there were three marketing channels, namely (I). Breeders – consumers. (II). Breeders – traders – consumers. (III). Breeders – collectors – retailers – consumers. The selling price is determined together with the estimation system by the collecting traders and is paid in cash. The biggest marketing margin is in channel III with a margin value of Rp. 444,000. The conclusion of this study is that the marketing of sheep on smallholder farms in Stabat District, Langkat Regency has been efficient.